People’s dwelling houses in Italy - SCHIAVI, A. (PSL Quarterly Review, 2014)
The article calls attention to the very serious problem arising from the extreme deficiency of housing for the under-privileged classes in Italy. After stressing the need of more efficient action in this field, the author illustrates the part that could be played in carrying out more extensive housing plans by the existing “Autonomous Provincial Institutes for People’s Houses”, and refers to their experience as organisers and administrators, which would fit them for a wise management of domestic and foreign capital. JEL: O18